2015
DOI: 10.1097/cmr.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

The cost of ipilimumab toxicity

Abstract: There are no published data on the costs associated with investigating and managing toxicity from ipilimumab treatment in patients with metastatic melanoma. Patients treated with ipilimumab at The Royal Marsden Hospital between 1 September 2010 and 1 April 2013 were identified. Data on demographics, investigations and survival outcomes were collected. Patients with grade 3 or higher immune-related adverse events were identified, and costs of investigating and managing toxicities in them were calculated on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…autoimmune-colitis or hypophysitis) documented with ipilimumab. Consistently, and according to a retrospective-single-center English cohort of patients ( n =110) treated with ipilimumab, immune-related adverse events do not represent a significant expense in comparison with the drug cost itself 49.…”
Section: Discussionmentioning
confidence: 81%
“…autoimmune-colitis or hypophysitis) documented with ipilimumab. Consistently, and according to a retrospective-single-center English cohort of patients ( n =110) treated with ipilimumab, immune-related adverse events do not represent a significant expense in comparison with the drug cost itself 49.…”
Section: Discussionmentioning
confidence: 81%
“…One study was a Canadian cost-effectiveness modeling analysis [ 21 ] ; 3 were economic burden analyses using published literature and physician interviews or a Delphi panel (1 conducted in the United States [US] [ 16 ] and 2 with a multicountry perspective [ 7 , 22 ] ); 2 were cost analyses using US claims data [ 15 , 23 ] ; and 1 was a United Kingdom (UK) medical records review. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ] Other included studies identified AEs through clinical trial publications and other relevant clinical publications, [ 21 ] package inserts [ 15 ] (also in consultation with a clinical expert [ 23 ] ), or medical records. [ 24 ] Table 1 summarizes the design of each included study, including the treatments considered and criteria applied for selection of AEs.…”
Section: Resultsmentioning
confidence: 99%
“…There is some evidence to suggest that those with more severe irAEs, which represent successful activation of the immune system may have an improved therapeutic response and cancer survival. [97][98][99][100] However, moderate to severe irAEs require treatment with steroids, PLEX, or IVIG to re-establish control over the immune response. One might expect that suppressing this response with steroids would affect survival.…”
Section: Diagnosismentioning
confidence: 99%